Alignment of Dietary Patterns With the Dietary Guidelines for Americans 2015–2020 and Risk of All-Cause and Cause-Specific Mortality in the Women's Health Initiative Observational Study. Issue 5 (16th December 2020) - George, Stephanie M; Reedy, Jill; Cespedes Feliciano, Elizabeth M; Aragaki, Aaron; Caan, Bette J; Kahle, Lisa; Manson, JoAnn E; Rohan, Thomas E; Snetselaar, Linda G; Tinker, Lesley F; Van Horn, Linda; Neuhouser, Marian L
Abstract: Poor diet quality is a leading risk factor for death in the United States. We examined the association between Healthy Eating Index-2015 (HEI-2015) scores and death from all causes, cardiovascular disease (CVD), cancer, Alzheimer disease, and dementia not otherwise specified (NOS) among postmenopausal women in the Women's Health Initiative Observational Study (1993–2017). This analysis included 59, 388 participants who completed a food frequency questionnaire and were free of cancer, CVD, and diabetes at enrollment. Stratified Cox proportional hazards models were fit using person-years from enrollment as the underlying time metric. We estimated multivariable adjusted hazard ratios and 95% confidence intervals for risk of death associated with HEI-2015 quintiles, with higher scores reflecting more optimal diet quality. Over a median of 18.2 years, 9, 679 total deaths 3, 303 cancer deaths, 2, 362 CVD deaths, and 488 deaths from Alzheimer disease and dementia NOS occurred. Compared with those with lower scores, women with higher HEI-2015 scores had an 18% lower risk of all-cause death and 21% lower risk of cancer death. HEI-2015 scores were not associated with death due to CVD, Alzheimer disease, and dementia NOS. Consuming a diet aligned with 2015–2020 US dietary guidelines may have beneficial impacts for preventing overall causes of death and death from cancer.